Motif Menggunakan Media Sosial Threads di Kalangan Mahasiswa Kota Surabaya - Firdauzan, Muhammad Daffa; Supriadi, Supriadi (DIGICOM : Jurnal Komunikasi dan Media, 2024)
This research aims to identify the motives that drive individuals to access the Threads social media platform among students in Surabaya City. The population of this study is 273,229, with a sample size of 100 respondents. The theoretical framework employed is the Uses and Gratification theory. The research methodology is quantitative descriptive research using a non-probability sampling technique with purposive random sampling. The data analysis technique involves univariate analysis, which includes simple tabulation of the questionnaire results filled out by the respondents. The obtained data are presented in the form of frequency distribution tables. In this study, the theory of media usage motives proposed by Papacharissi and Rubin is applied, encompassing Interpersonal Utility, Pass Time, Seeking Information, Entertainment, and Convenience motives. The findings reveal that Interpersonal Utility has an average score of 3.03, Pass Time has an average score of 3.34, Seeking Information has a score of 2.92, Entertainment has a score of 3.23, and Convenience has a score of 3.18.